Spatio-Temporal Climate and Agroclimate Diversities Over the Zagreb City Area - Bilandžija, Darija (Geographica Pannonica, 2019)
The Zagreb city is rich in green urban infrastructure that has an important role in climate change mitigation and adaptation. Knowledge on climate change and agroclimate has an important role in planning of green areas. Therefore, the aim is to evaluate the temporal and spatial diversities of agroclimate indicators over Zagreb city. Warming and no change in mean annual precipitation, as well as prolonged vegetation periods and reduced evapotranspiration were observed at all locations in the recent 1991-2018 compared to reference 1961-1990 period. The results indicate different intensity in climate change of observed indicators and existance of diffrences in indicators between city centre, suburb and hilly slopes thatshould be considered while planning green urban infracture.